Mobile application based on geolocation and Voice Assistant for private transportation of visually impaired individuals in Trujillo - Aguilar Bernabe, Junior Dicarlo; Rodriguez Murga, Aderhold Paul; Sierra-Liñan, Fernando (LACCEI, 2025)
This study presents an innovative mobile application that integrates geolocation and a voice assistant, specifically designed to improve private transportation experiences for visually impaired individuals in Trujillo, La Libertad. The main innovation lies in offering an inclusive and context-aware technological solution focused on user accessibility and autonomy. Using a quantitative, quasi-experimental design, the research evaluates the impact of this tool in three key dimensions: reduction of service request time, cost decrease, and increased user satisfaction. Results show a 36.84% reduction in average boarding time, a 33.33% decrease in service costs, and a significant improvement in user satisfaction—from deficient to excellent levels. These improvements highlight the transformative potential of accessible technology in enhancing mobility and social inclusion for visually impaired individuals. The study also emphasizes the importance of user-centered technological development, incorporating features such as voice commands and intuitive navigation to overcome traditional service access barriers. The findings support the proposed objectives and lay the groundwork for future research and development in accessible technologies, underscoring their role in building more inclusive societies.